PENGUATAN LITERASI DIGITAL DAN PEMASARAN ONLINE PADA KINERJA BUMDESA SEMBUNG GEDE, TABANAN - Ida Ayu Nyoman Yuliastuti; I Gusti Agung Ayu Istri Lestari; Komang Dean Ananda; Made Agung Raharja (JUIMA : JURNAL ILMU MANAJEMEN, 2025)
Village-Owned Enterprises (BUMDesa) play a crucial role in strengthening local economic resilience, yet many face challenges adapting to digital transformation. This study examines the influence of digital literacy and online marketing practices on the performance of Asta Dharma BUMDesa in Sembung Gede Village. Using a qualitative research approach, data were collected through in-depth interviews with BUMDesa managers, field observations, and analysis of organizational documents. The research findings indicate that BUMDesa managers' digital literacy remains at a basic level, characterized by limited skills in managing digital platforms, branding, and utilizing online marketing. Online marketing activities are still carried out in a rudimentary manner, without a structured strategy, using standard operating procedures, or a lack of dedicated human resources. These limitations significantly impact the visibility, competitiveness, and market reach of BUMDesa products. Although villages have strong economic potential, particularly in agriculture, local food products, and tourism, their integration into the digital market ecosystem remains weak. The study concludes that strengthening digital literacy is crucial for improving managerial capabilities, marketing effectiveness, and institutional performance. This study provides insights into the digital readiness of rural economic institutions and recommends sustainable capacity building, strategic digital marketing planning, and collaboration between stakeholders to improve the performance of BUMDesa in the digital era.